Penerapan Discharge Planning Menggunakan Audiovisual Dalam Pencegahan Infeksi Pascaoperasi Katarak Di Rumah Sakit X - desvianti, rizki azni; Mataputun, Donny Richard (Jurnal Kesehatan STIKes Sumber Waras, 2026)
ABSTRACT Background: Post-cataract surgery infection is a complication that can hinder the healing process and reduce the quality of patient's vision. Discharge planning using audiovisual media is considered effective because it is able to present information in an interesting, clear, and easy to understand manner. Objective: to analyze the application of discharge planning using audiovisual media in improving patient knowledge about preventing post-cataract surgery infection. Method: This study used an Evidence-Based Nursing (EBN) design with a case study approach. The research subjects were 10 respondents who were post-cataract surgery patients at Hospital X. Data collection was carried out by measuring the level of knowledge of respondents before and after being given discharge planning using audiovisual media. Results: The paired t-test showed a significant difference between the level of knowledge before and after the intervention with a p value = 0.001 (p < 0.05). The average knowledge score increased from 25.60 ± 8.83 to 46.10 ± 3.81 with a mean difference of 20.50. Conclusion: Discharge planning using audiovisual media is effective in increasing patient knowledge regarding post-cataract surgery infection prevention and can be used as an innovative nursing education method.